EVALUASI KINERJA CAMPURAN ASPAL MODIFIKASI EKSTRAKSI ASBUTON DAN FILLER ASBUTON SEBAGAI PENENTUAN KADAR MODIFIKASI OPTIMUM - Fitra - Ramdhani (LLDIKTI Wilayah X, 2019)
Abstract In line with the increase in road length, the asphalt demand in Indonesia is increasing as well. Asbuton can be used as a binder on pavement to replace oil asphalt. The levels of asphalt contained in asbuton is variated between 10% -40%. To increase the utilization of asbuton in Indonesia, the research on modification of asbuton in the mixture was carried out. This study aims to determine the effect of 60/70 pen asphalt mixture and modification pure asbuton T5 / 20 as a modification material with optimum T 5/20 asbuton filler content on mixed performance. This research was carried out by adding optimum asbuton filler level of 2.01% on the variation of pure T5 / 20 asbuton by 0%, 10%, 12%, 14%, 16%, 18%, 20% and 30% with a compaction temperature of 155 0C in mixture. Based on the results of the Marshall test, the performance of the modified material mixture that meets the general specification requirements on Bina Marga 2010 revision 3 which is the optimum level of extraction of asphalt T5 / 20 by 10% with filler asbuton T5 / 20 of 2.01%. This is evidenced by the Stability value of 2616 kg, the melting value of 2.85 mm, MQ value of 918 kg / mm, VIM value of 4.94%, VMA value of 15% and VFA value of 66.11% that meets the specification requirements.Keywords: Asbuton Extraction T5/20, Asbuton Filler T5/20, and Mixed Performance AbstrakSeiring dengan peningkatan panjang jalan maka kebutuhan aspal di Indonesia semakin meningkat. Asbuton dapat dimanfaatkan sebagai bahan pengikat pada perkerasan jalan menggantikan aspal minyak. Kadar aspal yang terkandung dalam asbuton bervariasi, antara 10%-40%. Untuk meningkatkan pemanfaatan asbuton di Indonesia maka dilakukan penelitian modifikasi asbuton dalam campuran. Penelitian ini bertujuan untuk mengetahui pengaruh campuran aspal pen 60/70 dan modifikasi asbuton murni T5/20 sebagai bahan modifikasi dengan kadar optimum filler asbuton T5/20 terhadap kinerja campuran. Penelitian ini dilakukan dengan penambahan kadar optimum filler asbuton sebesar 2,01% pada variasi asbuton murni T5/20 sebesar 0%, 10%, 12%, 14%, 16%, 18%, 20% dan 30% dengan suhu pemadatan 155 0C pada campuran. Berdasarkan hasil pengujian marshall diperoleh kinerja campuran bahan modifikasi yang memenuhi syarat spesifikasi umum bina marga 2010 revisi 3 yaitu kadar optimum asbuton murni T5/20 sebesar 10% dengan filler asbuton T5/20 sebesar 2,01%. Hal ini dibuktikan dengan nilai Stabilitas 2616 kg, nilai kelelehan 2.85 mm, nilai MQ 918 kg/mm, Nilai VIM 4.94%, Nilai VMA 15% dan Nilai VFA 66.11% yang memenuhi syarat spesifikasi. Kata kunci: Ekstraksi Asbuton T5/20, Filler Asbuton T5/20, dan Kinerja Campuran